2016
DOI: 10.1088/1742-6596/746/1/012055
|View full text |Cite
|
Sign up to set email alerts
|

Strain Induced Martensitic Transformation in Austempered Ductile Iron (ADI)

Abstract: The strain induced martensitic transformation in austempered ductile iron (ADI) has been investigated using high resolution neutron diffraction on samples compressed ex-situ to different plastic strains. In addition bulk texture measurements using neutron diffraction have been performed to calculate the orientation distribution of ferrite and austenite phases for different strain levels. Combing the detailed texture information with neutron diffraction pattern proved to be essential for quantitative phase anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Additionally, in the SADP, a typical crystallographic orientation relationship ([001]F//[011]A), labeled as Nishiyama-Wasserman (N-W)) between austenite and ferrite has been found and is depicted in Figure 2b. This also is in good agreement with recent texture measurements showing a similar orientation relationship in bulk samples [28,29].…”
Section: Ausferritic Microstructuresupporting
confidence: 93%
“…Additionally, in the SADP, a typical crystallographic orientation relationship ([001]F//[011]A), labeled as Nishiyama-Wasserman (N-W)) between austenite and ferrite has been found and is depicted in Figure 2b. This also is in good agreement with recent texture measurements showing a similar orientation relationship in bulk samples [28,29].…”
Section: Ausferritic Microstructuresupporting
confidence: 93%
“…Before and after, no significant deviation from a single Gaussian peak occurred. This indicates that the trends can be correctly approximated using a single Gaussian function, which we therefore kept for comparability to former results [ 10 , 47 ].…”
Section: Resultsmentioning
confidence: 80%
“…The metallographic examination of the specimens followed by tempering again showed that the material is isotropic and the metallography of all specimens is uniform. Spheroidal graphite and the ausferrite phase of the ADI alloy can be seen in the metallographic images [28]. The isotropic nature of the material and its uniformity over the entire cross-section are visible.…”
Section: Microstructurementioning
confidence: 91%